Describe The Understanding of Mathematical Concepts in Class VII Junior High School Students Regarding Objective Questions - Ndani, Yelza Elin; Erita, Selvia (DIDAKTIKA, 2023)
Understanding concepts is an important foundation for understanding principles and theories in various fields, including mathematics. Therefore, to understand principles and theories, students need to have a strong understanding of the concepts that form the basis of these principles and theories by using tests. The focus of this research is to analyze students' solutions to problems by looking at their ability to understand mathematical concepts in one of the state junior high schools in Pesisir Bukit district, Sungai Liuk. This type of research is qualitative research with a descriptive approach. Participants in this research were 16 class VII students. Data collection was carried out using concept understanding ability test instruments, observation and documentation studies. The results of the research show that there are differences in students' ability to understand mathematical concepts in solving the multiplechoice questions given.